2018
DOI: 10.1186/s12884-018-1709-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of the effectiveness of a breastfeeding training DVD on improving breastfeeding knowledge and confidence among healthcare professionals in China

Abstract: BackgroundDespite almost all babies being breastfed initially, the exclusive breastfeeding rate at six months is less than 30% in China. Improving professionals’ knowledge and practical skill is a key government strategy to increase breastfeeding rates. This study aimed to test the effectiveness of a breastfeeding DVD training method for clinicians on improving their knowledge and confidence in the breastfeeding support skills of teaching mothers Positioning and Attachment (P & A) and Hand Expression (HE).Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
9
0
4
Order By: Relevance
“…This promising positive effect of intervention is the only key for successful breastfeeding. Ma YY et al 16 and Wallace LM et al 17 both in their study found that video training for mother was effective methods of successful breast feeding.…”
Section: Discussionmentioning
confidence: 95%
“…This promising positive effect of intervention is the only key for successful breastfeeding. Ma YY et al 16 and Wallace LM et al 17 both in their study found that video training for mother was effective methods of successful breast feeding.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have previously found that breastfeeding training improves clinical skills and knowledge of healthcare professionals 5,9,22,47–49 . One randomised controlled trial found that a 14‐min educational DVD significantly increased professionals' skills in positioning and attachment and hand expressing 50 . To try to reduce the levels of breastfeeding modification after hospitalisation for bronchiolitis, a programme of training, as well as investment in more breast pumps and better signage and health promotion posters, was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,22,[47][48][49] One randomised controlled trial found that a 14-min educational DVD significantly increased professionals' skills in positioning and attachment and hand expressing. 50 To try to reduce the levels of breastfeeding modification after hospitalisation for bronchiolitis, a programme of training, as well as investment in more breast pumps and better signage and health promotion posters, was implemented. The researchers in the study found that following this programme, only 20% of mothers had unwanted breastfeeding modification after discharge from hospital, compared with 50% before the training programme.…”
Section: Breastfeeding Clinical Skillsmentioning
confidence: 99%
“…Interventions with telephone lactation counselling and education sessions followed by follow-up with phone calls did not show the aimed-for effect. Interventions with mixed effect were those that used—(1) short training movies [ 59 , 60 ], (2) WHO/UNICEF training material [ 28 , 38 ], and (3) existing community health workers (CHWs) [ 32 , 62 ].…”
Section: Discussionmentioning
confidence: 99%